Kyrgyz Republic : Access to Financial Services Policy Note - World Bank (World Bank, Washington, DC, 2013)
The purpose of this paper is to report on the level of access to formal financial services in the Kyrgyz Republic, assess the key obstacles to improving access, and make recommendations to overcome these obstacles. The paper is organized as follows. Sections II to IV examine the supply of financial services. Specifically, section II presents a profile of financial intermediation by banks, focusing their supply of financial services, particularly lending and deposits. Section III presents a profile of lending by Aiyl Bank, a specialized bank with a limited license, which is mandated to lend for agriculture. Section IV presents a profile of lending by non-bank financial institutions (NBFIs), including microfinance organizations (MFOs) and credit unions. Section V examines the demand side for financial services, drawing on enterprise surveys to assess firms' perceptions of their access to finance. Section VI presents a brief analysis of the impact of the events of April 2010 on access to finance. Section VII discusses key obstacles in increasing access to finance from banks and NBFIs. Section VIII concludes with policy recommendations that derive from the preceding analysis.